Métis Women’s Experiences in Canadian Higher Education - Bryanna Scott (Genealogy, 2021)
In Canada, there are three groups of Aboriginal people, also referred to as Indigenous peoples, and these include the First Nations, Inuit, and Métis. Although often thought of collectively, each has its distinct history, culture, and perspectives. The Métis people are mixed-culture people stemming from a long history of Indigenous people and European settlers intermixing and having offspring. Furthermore, the living history representing mixed ancestry and family heritage is often ignored, specifically within higher education. Dominant narratives permeate the curriculum across all levels of education, further marginalizing the stories of Métis people. I explore the experiences of Métis women in higher education within a specific region in Canada. Using semi-structured interview questions and written narratives, I examine the concepts of identity, institutional practices, and reconciliation as described by Métis women. Results assist in providing a voice to the Métis women’s experiences as they challenge and resist colonial narratives of their culture and expand upon a new vision of Métis content inclusion in higher education as reconciliation.